⁠ From Framing To Disinformation: Clippers and The Shift Of Messages Meaning on Social Media - Christiany Juditha; Josep J. Darmawan (Jurnal Komunikasi, 2025)
Short videos of public officials that are then edited by clippers are a big source of false information on social media. These clips change important parts of the footage, which makes people angry because it changes the message and story. This study examines the creation of disinformation via clipper-generated content, utilizing qualitative methodology and framing analysis. The findings indicate that the primary method of disseminating disinformation involves deliberately altering or omitting contextual cues in short-form videos. This pattern is clear in the cases of Finance Minister Sri Mulyani and Member of Parliament Rahayu Saraswati. In the first case, the fiscal context was left out on purpose, and in the second case, the creative-economy context was changed. Consequently, both officials were recontextualized in manners that suggested they belittled educators or exhibited personal hubris. People are less likely to think about the real, structural parts of the problems and more likely to think about moral and emotional judgments of individual people when they change the way they think about these issues. People think the problems are personal flaws instead of policy issues, which makes calls for resignation and makes current policy solutions less important. The phenomenon also shows what could be called a "clipper mentality": a way of making and consuming content that puts sensational visual snippets ahead of understanding the context. This tendency makes structural problems into moral attacks on people, which makes online discussions more divided.